Drug trapping and delivery for Alzheimer's diagnosis - M. A. Jalil; Surachart Kamoldilok; T. Saktioto; C. T. Ong; Preecha P. Yupapin (My University, 2012)
In this investigation, a new design based on a PANDA ring resonator as an optical trapping tool for tangle protein, molecular motor storage, and delivery is proposed. The optical vortices are generated and the trapping mechanism is controlled in the same way as the conventional optical tweezers. The trapping force is produced by a combination of the gradient field and scattering photons. The required molecular volume is trapped and moved dynamically within the molecular network. The tangle protein and molecular motor can be transported and delivered to the required destinations for Alzheimer's diagnosis by molecular buffer and bus network.
Keywords: Tweezers; On demand; Tangle; Trap (plumbing); Orbital Angular Momentum in Optics